THE EFFECT OF ACCESS TO EDUCATION AND ACCESS TO HEALTH ON POVERTY LEVELS IN INDONESIA FROM AN ECONOMIC PERSPECTIVE ISLAM 2015-2024 - Galuh Ramadhan; Wahyu Iryana; Gustika Nurmalia (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2026)
This study aims to analyze the effect of access to education and healthcare on poverty levels in Indonesia from an Islamic economics perspective during the 2015–2024 period, using a quantitative approach and multiple linear regression analysis based on secondary data obtained from the Central Bureau of Statistics (BPS). The results indicate that access to education has a negative and significant effect in reducing poverty, while access to healthcare has a negative but not statistically significant effect. Simultaneously, both variables have a significant influence and are able to explain a large proportion of the variation in poverty levels. From the perspective of Islamic economics, education and healthcare are considered essential factors in improving human resource quality, promoting welfare, and achieving social justice in order to reduce poverty.